2017
DOI: 10.20448/journal.509.2017.43.81.91
|View full text |Cite
|
Sign up to set email alerts
|

The Role of an Aligned Curriculum Design in the Achievement of Learning Outcomes

Abstract: The importance of learning outcomes (LOs) as a central component of LOs-based curriculum design has been emphasized by many higher education experts and researchers (Biggs, 1999;Adam, 2006;Kennedy et al., 2006;Biggs and Tang, 2007;Warnier et al., 2010). However, the important role played by program and course curriculum design in securing a successful shift from the intended learning outcomes (ILOs) to the achieved learning outcomes (ALOs) or simply (LOs) still requires further attention. This study highlights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
1
11
0
1
Order By: Relevance
“…This is in line with the literature on banks' risk taking where more risk-taking makes banks less stable and increased chances of default. This is also in line with the literature on competition and banking stability where Lerner, the measure of market power, is used as an inverse measure of competition and a positive relationship is found thus competition-fragility view is supported, implying that more market power makes banks more stable (Jiménez et al, 2013;Alfauzan and Tarchouna, 2017;Kabir and Worthington, 2017;Leroy and Lucotte, 2017;Danisman and Demirel, 2018;Risfandy et al, 2018).…”
Section: Regression Resultssupporting
confidence: 86%
“…This is in line with the literature on banks' risk taking where more risk-taking makes banks less stable and increased chances of default. This is also in line with the literature on competition and banking stability where Lerner, the measure of market power, is used as an inverse measure of competition and a positive relationship is found thus competition-fragility view is supported, implying that more market power makes banks more stable (Jiménez et al, 2013;Alfauzan and Tarchouna, 2017;Kabir and Worthington, 2017;Leroy and Lucotte, 2017;Danisman and Demirel, 2018;Risfandy et al, 2018).…”
Section: Regression Resultssupporting
confidence: 86%
“…17 Additionally, this study fulfilled the recommendations of the National Qualification Framework for higher education in Saudi Arabia, 18 since all the assessment types consider the appropriate types of assessments to be used in the learning process in different domains. 19 A study conducted by Ketteridge and Marshall 20 also aligned related objectives and learning styles to specific disciplines and types of assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Biggs and Tang (2011), as in the Saudi context, stressed the importance of learning outcomes as central to constructive alignment: "Get them right and the decisions as to how they are to be taught and how they may be assessed follow" (p. 104). Alfauzan and Tarchouna (2017) studied the application of constructive alignment on a theoretical translation course at a Saudi university and found that a well-designed curriculum can maximize learning outcomes.…”
Section: B Curriculum Alignment In Contextmentioning
confidence: 99%